Improving Fine Motor Development with Collage Techniques in Group B Children - Arina, Putri; Yenti, Yesni; Ratnasari, Lili (CV. Strata Persada Academia, 2024)
This study investigates the impact of collage activities on the fine motor skills development of children in Group B at Raudhatul Jannah Kindergarten, Jorong Koto Baru Nagari Aie Winter, Lembah Gumanti District, Solok Regency. Recognizing that early childhood education significantly influences lifelong development, this research employs Classroom Action Research (CAR) to enhance learning outcomes and address classroom challenges. The study involved 15 children (8 boys and 7 girls) during the first semester of the 2023/2024 academic year, using observation and documentation methods to assess fine motor skill improvements based on the Indonesian Ministry of Education and Culture standards. The research comprised two planning cycles, implementation, observation, and reflection, with collage activities to stimulate fine motor skills. The results demonstrated a significant enhancement in the children’s fine motor abilities across both cycles. By the end of the second cycle, all aspects of fine motor development had shown considerable improvement. Additionally, the collage technique fostered cognitive development, brain training, and increased patience and interest among children. The findings suggest that integrating collage activities into early childhood education can effectively support the holistic development of fine motor skills and other related cognitive abilities. This approach provides a valuable method for educators to enhance early childhood learning experiences.